Temperature dependence of dielectric properties of blood at 10 Hz–100 MHz - Wang, Weice; Li, Weichen; Liu, Benyuan; Wang, Lei; Li, Kun; Wang, Yu; Ji, Zhenyu; Xu, Canhua; Shi, Xuetao (Frontiers in Physiology, 2022)
The temperature dependence of the dielectric properties of blood is important for studying the biological effects of electromagnetic fields, electromagnetic protection, disease diagnosis, and treatment. However, owing to the limitations of measurement methods, there are still some uncertainties regarding the temperature characteristics of the dielectric properties of blood at low and medium frequencies. In this study, we designed a composite impedance measurement box with high heat transfer efficiency that allows for a four/two-electrode measurement method. Four-electrode measurements were carried out at 10Hz-1MHz to overcome the influence of electrode polarization, and two-electrode measurements were carried out at 100Hz-100MHz to avoid the influence of distribution parameters, and the data was integrated to achieve dielectric measurements at 10Hz-100MHz. At the same time, the temperature of fresh blood from rabbits was controlled at 17-39 ℃ in combination with a temperature-controlled water sink. The results showed that the temperature coefficient for the real part of the resistivity of blood remained constant from 10 Hz to 100 kHz (-2.42 %/°C) and then gradually decreased to -0.26 %/°C. The temperature coefficient of the imaginary part was positive and bimodal from 6.31 kHz to 100 MHz, with peaks of 5.22 %/°C and 4.14 %/°C at 126 kHz and 39.8 MHz, respectively. Finally, a third-order function model was developed to describe the dielectric spectra at these temperatures, in which the resistivity parameter in each dispersion zone decreased linearly with temperature and each characteristic frequency increased linearly with temperature. The model can estimate the dielectric properties at any frequency and temperature in this range, and the maximum error is less than 1.39%, thus laying the foundation for subsequent studies.